Analysis of genetic parameters and correlation for yield and quality traits in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
A set of 53 Indian mustard (Brassica juncea L) genotypes that include 40 crosses and 13 parents were evaluated for genetic variability and correlation for yield and quality traits during the Rabi season of 2014-15. The crosses were developed in line x tester design involving 8 lines and 5 testers (quality trait donors) during Rabi 2013-14.The study was undertaken to generate genetic information for seed yield per plant (g),1000-seed weight (g), days to maturity, oil content (%), saturated fatty acid (%), oleic acid (%), linoleic acid (%), linolenic acid (%), erucic acid (%) and glucosinolate content (μmoles/g of oil-free seed meal). Moreover, magnitude of relationships among these characters was also measured. Significant differences were observed for all the characters among the genotypes, which revealed the presence of sufficient variability for the characters. The phenotypic coefficient of variation (PCV) for all the characters was found to be higher than genotypic coefficient of variation (GCV). High PCV for erucic acid, oleic acid and glucosinolate content showed the significance of additive gene action. High heritability estimates coupled with high genetic advance as per cent of mean recorded for erucic acid and oleic acid also indicated the significance of additive genes action for the inheritance of these traits. Among the different characters seed yield per plant recorded lowest heritability estimates and low genetic advance indicating predominance of non-additive gene effects for this trait. Oleic acid was found negatively and significantly correlated with erucic acid (-0.893**) and oil content (-0.639**), while it had significant and positive correlation with linoleic acids (0.837**) and days to maturity (0.622**). Erucic acid was negatively and significantly correlated with the rest of the fatty acids. It had positive association with oil content (0.600**). Breeding for the development of lines with high oleic acid should be focused owing to its high extent of variability, heritability, genetic advance and negative correlation with erucic acid.